Disobedience [videorecording (DVD)] - Lelio, Sebastián, 1974-; Weisz, Rachel, 1970-; McAdams, Rachel, 1978-; Nivola, Alessandro; Alderman, Naomi (Universal Pictures Home Entertainment, 2018)
A woman returns to the community that shunned her for her attraction to a childhood friend. Once back, their passions reignite as they explore the boundaries of faith and sexuality.